Patterns of dental emergence in early anthropoid primates from the Fayum Depression, Egypt. (17th February 2018) - Miller, Ellen R.; Gunnell, Gregg F.; Seiffert, Erik R.; Sallam, Hesham; Schwartz, Gary T.
Abstract: Paleontological field work in the Fayum Depression of Egypt has produced a remarkable diversity of fossil anthropoids, and this, combined with advances in genetic analyses of living anthropoids, has led to establishment of a temporal and phylogenetic framework for anthropoids that is achieving some degree of consensus. Less well understood are the evolutionary mechanisms and selective factors behind the origin and early diversification of anthropoids. One area that has remained under explored is investigation into the life history patterns of early anthropoids, a major omission given that understanding patterns of growth and development is essential for interpreting the paleobiology of fossil species. Here we detail dental emergence sequences for five species in four families of early anthropoid primates from the Fayum, and use these data to test Schultz's Rule concerning the timing of emergence of molars versus premolars in mammals. Two important results are generated: (1) only one species had a dental eruption sequence identical to that observed among crown catarrhine primates; and (2) in all cases, the permanent canine was the last post-incisor dental element to fully erupt, a finding that may be significant for interpreting early anthropoid behavioral strategies.